Progression along the invasion curve: silver carp growth slows temporally in two Missouri River tributaries - Justin D. Harms; Kenny R. Jimerson; Josh M. Schmidt; David O. Lucchesi; Benjamin J. Schall; Alison A. Coulter (Aquatic Invasions, 2024)
Silver carp (Hypophthalmichthys molitrix Valenciennes, 1844) have been invading North American rivers for decades, often altering zooplankton community structure and impacting native fishes. Silver carp invaded eastern South Dakota tributaries of the Missouri River in the early 2000s. Changes in dynamic rate functions can occur as invasive populations move to the latter stages of the invasion curve, but direct temporal assessments of silver carp populations are limited. Our objectives were to compare current growth of silver carp 1) between the Big Sioux and James rivers in South Dakota and 2) with previous growth recorded from the early stages of invasion (2009–2012) in these rivers. We collected silver carp in May and June of 2020–2022 using boat electrofishing and cast netting. We extracted lapilli otoliths for consensus aging from 99 and 82 silver carp from the Big Sioux and James rivers, respectively. We evaluated growth for each population using Bayesian von Bertalanffy models and compared posterior mean length at ages 2–5 to determine the probabilities of differences between rivers and with estimates from the introduction stage. Posterior estimated mean L∞ values were similar between the Big Sioux (714 mm) and James rivers (709 mm); however, the probability that the posterior mean K estimate was greater for silver carp in the James River (0.271) than the Big Sioux River (0.248) was >99.9%. Estimated mean lengths at age 2 were larger in the Big Sioux and James samples than during the introduction stage, but mean lengths at ages 3–5 were smaller. Changes in growth characteristics indicate that growth has slowed in the current establishment stage of invasion from the earlier introduction stage.